Pengaruh PBB, Pajak Restoran Dan Pajak Hiburan Terhadap Paddki Jakarta 2014-2016 - Alfian Yanuar, Sukrisno Agoes (Jurnal Paradigma Akuntansi, 2019)
The purpose of this study is to examine the effect of Rural and Urban Land and Building Taxes, restaurant tax and entertainment tax on DKI Jakarta Regional Revenue in 2014-2016. The sampling technique uses purposive sampling. The sample of this study is 43 sub-districts of DKI Jakarta which are spread in 5 municipalities that representing DKI Jakarta and also representing all taxpayers who contributed to got those Regional Original Income (PAD). This study uses logistic regression analysis using the SPSS version 25 statistical program. The results obtained through the study state that Rural and Urban Land and Building Taxes, restaurant taxes and entertainment taxes have a significant effect on DKI Jakarta Regional Revenue (PAD) in 2014-2016. However, the entertainment tax has a significant negative effect on DKI Jakarta PAD